Conservation interventions are required to improve bird breeding performance in artificial wetlands. (February 2023) - Cheng, Chuyu; Ma, Zhijun
Abstract: Along with ongoing loss of natural habitats, expanding artificial (human-made or human-managed) habitats provide alternative habitats for many wildlife species. Many studies have investigated wildlife diversity in artificial habitats, but whether the use of artificial habitats has fitness consequences remains unclear. We compiled global data on bird breeding performance, which is a fitness-related indicator, in a variety of artificial wetland types through a literature review. We first analysed the proportion of breeding failures caused by human activities. Then we conducted a meta-analysis to compare the breeding performance of birds in artificial and natural wetlands to investigate the effects of conservation interventions and nest location on the breeding performance of birds in artificial wetlands. Results showed that human-induced breeding failures are common in artificial wetlands, such as nest trampling and damage caused by production practices. On average, 50.6 % of studies recorded breeding failures caused by human activities, contributing to 37.0 % of total breeding failures in those studies. We found no significant difference on the breeding performance of birds in artificial and natural wetlands. However, conservation interventions improved the breeding performance of birds in artificial wetlands, especially for ground-nesting species, whose breeding failure rates in artificial wetlands without conservation interventions were on average 42.9 % (95 % CI: 18.1 % to 59.7 %) higher than in natural wetlands. Given the ongoing expansion of artificial habitats, our study highlights that while protecting the natural habitats of biodiversity hotspots, it is also essential to conduct conservation interventions in artificial habitats to fully exploit their functions in supporting biodiversity.